Values Generated by Projects in Organizations - Jolanta WALAS-TRĘBACZ; Katarzyna BARTUSIK (Communications of International Proceedings, 2021)
The paper attempts to fill the existing research gap in the scope of project value management and, in particular, to show the type of values generated by implemented projects for the organization and to indicate the role that individual groups of stakeholders play in the process of capturing the project value created. The paper reviews the literature, which allowed a synthetic presentation of approaches to defining project value and project value management. The paper contains the results of empirical research conducted among the owners and top management of 80 organizations operating in Poland on the basis of the developed methodology and a selected research instrument in the form of a questionnaire. The statistical analysis of the collected results was performed with the use of the Statistica PL 13.3 package. The main purpose of the research was to identify the type of values generated by project, determining the importance of basic values (economic, social, ecological) in the created types of project and showing the importance of the category of values achieved through the implementation of projects for the surveyed organizations.
Keywords: Project Value; Project Value Management; Value Types; Stakeholders.